Scrutinising the of ESL preferences in literature approaches and activities: from the lenses teachers - Ashairi Suliman; Melor Md Yunus; Mohamed Yusoff Mohd Nor (Penerbit Universiti Kebangsaan Malaysia, 2019)
Literature learning is associated with language and linguistics. It serves as a means to develop language proficiency and becomes the avenue to express appreciation for cultural knowledge. However, the teaching of literature may not succeed if unsuitable approaches are employed. Therefore, it requires suitable activities to be conducted in a lesson which this study aims to examine. By employing questionnaire and interviews as the research instruments, 271 English as Second Language (ESL) teachers were involved in this study. This study discovered that using simple terms in giving explanation approach was highly preferred by the respondents besides conducting a comprehension questions activity. Further results were discussed in the paper. The interview responses consolidated the findings. To summarise, teachers should design more creative and appealing activities that suit the approaches employed as a platform to inculcate students’ interest in literature lessons.